2019
DOI: 10.1111/efp.12555
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Phlebiopsis gigantea in wood of seven conifer species

Abstract: Heterobasidion parviporum and Heterobasidion annosum are widely distributed root‐rot fungi that infect conifers throughout Europe. Infection of conifer stumps by spores of these pathogens can be controlled by treating fresh stumps with a competing non‐pathogenic fungus, Phlebiopsis gigantea. In this study, growth of three Latvian strains of P. gigantea and the biological control agent ‘Rotstop’ strain was evaluated in stem pieces of Norway spruce, Scots pine, lodgepole pine, Douglas‐fir, Weymouth pine, Siberia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
(49 reference statements)
2
11
0
Order By: Relevance
“…In addition, it has been reported that larger amounts of triglycerides were extracted from sapwood, compared to heartwood in Pinus species 9 . The growth rate of P. gigantea greatly varies depending on softwood species, i.e., it grows well on Pinus species but not on spruce, larch and fir 36 . Therefore, PgLip19028 is thought to play important roles in the penetration into Pinus sapwood by P. gigantea , and there would be value in examining P. gigantea responses to different extractives from various softwood species in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that larger amounts of triglycerides were extracted from sapwood, compared to heartwood in Pinus species 9 . The growth rate of P. gigantea greatly varies depending on softwood species, i.e., it grows well on Pinus species but not on spruce, larch and fir 36 . Therefore, PgLip19028 is thought to play important roles in the penetration into Pinus sapwood by P. gigantea , and there would be value in examining P. gigantea responses to different extractives from various softwood species in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the risk of secondary infections via root contacts from these thinned trees, a 3 m buffer zone between trees used in this experiment and old stumps was implemented. Commercial Rotstop ® (Phlebiopsis gigantea strain VRA 1835) and Latvian P. gigantea strain 422 (in text P. gigantea 422), initially isolated from Norway spruce and previously characterized in vitro on malt agar for growth, asexual spore production and antagonism against H. annosum and H. parviporum [42,43], were used as BCA for stump treatments.…”
Section: Plant and Fungal Materialsmentioning
confidence: 99%
“…These results are in agreement with those obtained in other studies, where the efficacy of urea and P. gigantea were similar [5,20,29]; however, urea has been documented to have higher efficacy in comparison to P. gigantea in some studies [26,33,34]. Moreover, development of P. gigantea depends on (i) stump treatment coverage quality [28,30,53]; (ii) stump and root wood moisture content, which in turn depend on the humidity during the treatment period [53], weather conditions and seasonality [54][55][56]; (iii) growth characteristics of different P. gigantea isolates [43]; (iv) enzymatic activity of the fungi; (v) the characteristics of the wood; and (vi) the richness of the fungal biota [57]. Furthermore, Wang et al [29] found that treatment of Larix x eurolepis stumps with urea resulted in more stable effects in control of Heterobasidion than using BCA.…”
Section: Effects Of Treatments On Heterobasidion Incidence and Stump Colonizationmentioning
confidence: 99%
“…The Latvian strains of P. gigantea were selected based on the characteristics obtained in laboratory (Tab. 1) and field experiments (unpublished data except the data concerning the Latvian strain G1 - Kenigsvalde et al 2016, Zaluma et al 2019. For preparation of treatment suspension, each P. gigantea strain was cultured in six Petri dishes on malt extract agar medium for 3 weeks at 20 °C in dark conditions.…”
Section: Preparation Of Treatment Suspensionsmentioning
confidence: 99%
“…laricio stumps, P. gigantea proved to be more efficient against infection caused by Heterobasidion conidiospores than by basidiospores (Kuhlman & Hendrix 1964, Tubby et al 2008. As the host tree species influences the control effect of P. gigantea as well as susceptibility to Heterobasidion species (Thomsen & Jacobsen 2003, Garbelotto & Gonthier 2013, Gonthier 2019, Zaluma et al 2019, the results obtained in one tree species may not be applicable to others. Besides Scots pine stumps, Norway spruce stumps are the most important targets of stump treatment in northern and most of central Europe.…”
Section: Introductionmentioning
confidence: 99%